Reviewing the Blockchain’s Framework and its Role in Sustainable Industries - Ahamed, N. Nasurudeen; Alam, Tanweer; Benaida, Mohamed (JOIN (Jurnal Online Informatika), 2025)
Blockchain technology is often regarded as a highly advanced and pioneering breakthrough in modern times. Blockchain technology is a distributed ledger that uses encryption to prevent security breaches and securely stores data across many systems. This facilitates collaborative transactions by providing a solitary, dependable reference point, revealing the purported trust intermediaries. This study aims to investigate the core principles of blockchain technology and assess its potential to support sustainability across various sectors. It seeks to examine how blockchain technology enhances reliability, effectiveness, and transparency in industries such as supply chain management and the energy sector. This study addresses these concerns by assessing the valuable applications, advantages, and drawbacks of blockchain in promoting sustainable industrial practices. Bitcoin and other cryptocurrencies rely on hashing as the foundation of their blockchain technology. Blockchain is a digital ledger that documents and tracks financial transactions. Blockchain technology has become prevalent across several sectors, encompassing artificial intelligence, machine learning, and the Internet of Things. Therefore, once the blockchain is prepared for dissemination, the data cannot be modified by anyone. This implies that it is immutable. Hyperledger offers a neutral platform for facilitating collaborative operations among organisations that frequently engage in competitive activities. Hyperledger is specifically designed to provide explicit support for blockchains as a means of business agreements. Authorisation is a prerequisite for a framework, ensuring that only those with proper authorisation can join the organisation. The ability of the manager to impose limitations on user access to the blockchain enhances security measures. Moreover, instead of being universally accessible through online platforms, trades are maintained secretly, limiting access to only essential participants. Using distributed code bases and open-source record upgrades facilitates enhanced efficiency in corporate activities. The fast expansion of blockchain technology has led to its widespread adoption across several industries worldwide. Illustrations encompass various domains, including logistics, copyright, finance, medicine, and supply chain management. Furthermore, we offer an introductory overview of blockchain technology, encompassing topics such as different types of blockchains and their utilisation across many sectors.